Manes & Kopi / Aisyah Muhd Azri Baptist and Nur Syafia Mohd Sari - Muhd Azri Baptist, Aisyah; Mohd Sari, Nur Syafia (2022)
Manes & Kopi is founded by partners, Miss Aisyah Binti Muhd Azri Baptist and Miss Nur Syafia Binti Sari. Te company was started in November 2021 and is based in Jalan Duta, Kuala Lumpur's. Manes & Kopi was established with the goal of providing delicious, creamy and superb flavoured coffee drinks and various flavoured milkshakes to the people at Klang, Valley at an affordable prices. Manes & Kopi launched a business so that many people may enjoy the creamy taste of our coffee and milkshakes, as there are still few cafes of vendors serving coffee drinks and milkshakes in this area.